The Effectiveness of the Teaching Style of the Command Self Check on the Application of the Futsal Parallel Tactic Pattern - Ganjar Cahya Ramadhan; Iif firmana; Boby Agustan (Journal of Physical Education and Sport Science, 2019)
Ganjar Cahya Ramadhan (162223097), Efektivitas Gaya Mengajar Command dengan Self Check Terhadap Penerapan Pola Taktik Paralel Permainan Futsal Di Ekstrakurikuler SMP Negeri 2 Kuningan. Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi (PJKR), 2020, 66 halaman. This Research is based on the mistakes learning of attack strategy in Futsal, during matches or training. The Purpose of this research to know capability of students learn about attack strategy in Futsal, combined with two different teaching styles, that is command and self check.. This Research uses experimental by design pre-experimental with form intact-group comparison. The technique used is the test technique. The instrument used is Game Peformance Assessment Instrument (GPAI). The result from using teaching style command is (C=33,58) and then the result from using teaching style self check is (S= 29,33) results from the level of 0.05 and get the results of t count = 0.280, t table 1,795 or t count smaller than t table . Based on the results it can be concluded teaching style command is more effective compared with teaching style self check to practice attack strategy futsal in extracurricular Junior High School 2 Kuningan..